Development of vaccines for prevention of peste-des-petits-ruminants virus infection. (May 2020) - Jia, Xue-Xia; Wang, Hui; Liu, Ying; Meng, De-Mei; Fan, Zhen-Chuan
Abstract: Peste des petits ruminants (PPR) is a highly contagious and fatal disease of small ruminants, particularly sheep and goats. This disease leads to high morbidity and mortality of small ruminants, thus resulting in devastating economic loss to the livestock industry globally. The severe disease impact has prompted the Food and Agriculture Organization of the United Nations (FAO) and the World Organization for Animal Health (OIE) to develop a global strategy for the control and eradication of PPR by 2030. Over the past decades, the control of PPR is mainly achieved through vaccinating the animals with live-attenuated vaccines, e.g., rinderpest vaccines. As a closely related disease to PPR of large ruminants, rinderpest was eradicated in 2011 and its vaccines subsequently got banned in order to keep rinderpest-free zones. Consequently, it is desirable to develop homologous PPR vaccines to control the disease. The present review summarizes the objectives of PPR control and eradication by focusing on the homologous PPR vaccines. Highlights: Currently used Peste-des-Petits-Ruminants (PPR) vaccines were reviewed. Currently used PPR vaccines resisting different viral lineages were discussed. Development of homologous PPR vaccines were concentrated. Reverse genetics for developing live marker PPR vaccines was described.